Tax effort and oil royalties in the Brazilian municipalities - Fernando Antonio Slaibe Postali (EconomiA, 2015)
This paper estimates a stochastic production frontier, to investigate whether municipalities covered by oil royalties in the last decade have reduced their tax effort in Brazil. The issue is relevant to the prospect of a substantial increase in these revenues and the new rules for distribution of the funds, established by Law No. 12.734/2012. The inputs were provided by personnel and capital expenditures, whereas the product was defined as the municipal tax collection. With the purpose of overcoming the endogeneity problems due to reverse causality of output on inputs, we used the lagged independent variable as instruments in the inefficiency equation. The data set is composed of a panel of Brazilian municipalities from 2002 to 2011. The results indicate that oil revenues have a negative impact on the estimated efficiencies, signaling reduced fiscal effort by the benefiting municipalities. – – Este artigo estima uma fronteira estocástica de produç\~ao a fim de investigar se os municípios beneficiados com royalties do petróleo na última década reduziram seu esforço tributário no Brasil. O tema é relevante devido à perspectiva de aumentos substanciais nestas receitas e às novas regras para distribuiç\~ao destes recursos, definidos pela Lei 12.734/2012. Os insumos foram definidos pelas despesas de pessoal e de capital, enquanto o produto foi definido como a arrecadaç\~ao tributária municipal. Com o propósito de contornar potenciais problemas de endogeneidade devido à possível causalidade reversa de produtos nos insumos, as defasagens das variáveis independentes foram usadas como instrumento na equaç\~ao de ineficiência. O banco de dados é composto por um painel de municípios brasileiros observados de 2002 a 2011. Os resultados indicam que as receitas do petróleo possuem um impacto negativo significativo nas ineficiências estimadas, sinalizando uma reduç\~ao do esforço fiscal nos municípios beneficiados.
Keywords: H21; H71; Q38; 330; Oil windfalls; Stochastic frontier analysis; Tax effort; Municipalities; Endogeneity